Sosialisasi Peraturan Daerah Sempadan Sungai Dalam Rangka Pengendalian Banjir Sungai Maros - Rita Tahir Lopa (Faculty of Engineering UNHAS, 2020)
Maros Regency is one of the regencies in South Sulawesi Province whose river management system is not optimal yet. Based on this case, the Maros River flooding problem in Maros Regency must be dealt with as soon as possible in a good and correct manner and community participation is needed in terms of understanding river border regulations. The purpose of this activity is to provide socialization to the community to increase community knowledge about river border regulations. The method is used to achieve the stated goals and targets is to carry out river schools which are expected to be useful for the local community. Activities undertaken will involve the community. The implementation of this community service activity, in the form of socialization of river boundary regulations in the context of flood control, is expected that community knowledge about river border will increase and patterns of community behavior regarding the handling of river border areas can be increased and will have a positive impact on improving river management by the community. The knowledge that is possessed is expected to be transmitted and become an example for the community around Maros Regency